Mathematical Model of the Spread of Middle East Respiratory Syndrome- Corona Virus (MERS-CoV) - Eriza, Suci Okta (Journal of Mathematics UNP, 2024)
ABSTRACT           Viruses are parasites or living things whose life depends on other living things, microscopic (invisible to the eye) that infect the cells of biological organisms. There are many diseases caused by viruses, one of which is Middle East Respiratory Syndrome-Corona Virus (MERS-CoV), which is a subtype of the corona virus that has never been found to infect humans before.          This study aims to form a mathematical model that can describe how the Middle East Respiratory Syndrome-Corona Virus (MERS-CoV) spreads to help control measures.          This research is a basic research using descriptive method, namely by analyzing the theories relevant to the problem. This research begins by forming a mathematical model of the spread of Middle East Respiratory Syndrome-Corona Virus (MERS-CoV) then looking for a fixed point and analyzing the stability of that fixed point and interpreting the analysis results obtained from the model.          The model obtained is in the form of a system of differential equations consisting of three equations and has two fixed points. From the analysis, it is found that the factor that affects the spread of Middle East Respiratory Syndrome-Corona Virus (MERS-CoV) in a population is the level of transmission. The higher the level of transmission and the lower the cure rate for an infected individual, the more MERS-CoV spread will be. Keywords: Mathematical Model, Middle East Respiratory Syndrome – Corona Virus (MERS-CoV)